ACE2 a double-edged sword? - Campagnole Santos, Maria Jose (2020)
Angiotensin-converting enzyme 2 (ACE2) is the binding protein/receptor used by the new SARS-CoV-2, which causes 2019 coronavirus disease (COVID-19), to enter host cells [1,2]. In 2003, Li and colleagues [3] at the Harvard Medical School, USA had previously described that a protein (spike proteins - S1 domain) da família do coronavirus binds efficiently to ACE2 [3,4]. From binding to ACE2, the virus envelope fuses into the host cell membrane allowing its genetic material entering the cell and replicate, triggering severe respiratory disease, including acute respiratory distress syndrome (ARDS), a devastating lung disease with high mortality rates (3060%).